Litter Productivity Dynamics in Segara Anakan Mangrove Forest, Cilacap, Indonesia - Kresnasari, Dewi; Zainuri, Muhammad; Muskananfola, Max Rudolf; Pribadi, Rudhi; Wiarta, Rinto (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2025)
Mangrove litter is a critical component of the nutrient cycle, reflecting soil fertility and water quality within the mangrove ecosystem. This study investigates the dynamics of litter productivity in the Segara Anakan mangrove forest in Cilacap. The study area is divided into two locations with three points, with five litter traps installed at each point. Sonneratia caseolaris dominates vegetation characteristics at Station 1, while Station 2 has more diverse vegetation, including Sonneratia caseolaris, Aegiceras corniculatum, Acanthus ilicifolius, Derris trifoliata, Rhizophora mucronata, Avicennia alba, and Avicennia marina. Sampling follows seasonal changes in Indonesia, covering June 2023 to March 2024. The primary data for this study include aboveground litterfall production, estimated using litter traps, and the litter layer on the forest floor collected through soil transects. Secondary data comprise weather measurements, including air temperature, rainfall, wind speed, and humidity. Litterfall and litter layer were collected four times: June (dry season), September (transition from dry to rainy season), December (rainy season), and March (transition from rainy to dry season). The results indicate a total litter productivity of 18.99 tonnes ha-1 yr-1. The lowest litter production was observed in September, while the highest was in March. Leaf litter contributed the most, accounting for 71.49%, followed by twigs at 19.19%, flowers/fruits at 8.31%, stipules at 0.62%, and the lowest portion from other unidentified materials at 0.39%. Litter productivity shows a strong correlation (0.99) with rainfall. The main factors influencing litter productivity include environmental factors, primarily rainfall, and physiological factors, such as flowering and fruiting phenology.